2022
DOI: 10.5812/ijpr-130342
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Lysosome-Related Genes Associated with Drug-Resistant Breast Cancer Using Computational and Systems Biology Approach

Abstract: Background: Drug resistance in breast cancer is an unsolved problem in treating patients. It has been recently discussed that lysosomes contribute to the invasion and angiogenesis of cancer cells. There is evidence that lysosomes can also cause multi-drug resistance. We analyzed this emerging concept in breast cancer through computational and systems biology approaches. Objectives: We aimed to identify the key lysosome-related genes associated with drug-resistant breast cancer. Methods: All genes contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…there was signi cant heterogeneity in gene expression among different subpopulations. For example, GJA1, which was the increased expression in subpopulation 5, has the potential to serve as a cancer biomarker for prognosis, as well as a therapeutic target to inhibit metastasis and chemoresistance in cancer [19]. Subpopulations 14 and 15 exhibited high expression of GRB7, which is often co-ampli ed and overexpressed with HER2 in human breast cancers [20].…”
Section: Functional Status Of the Breast Cancer Clusters And Subpopul...mentioning
confidence: 99%
“…there was signi cant heterogeneity in gene expression among different subpopulations. For example, GJA1, which was the increased expression in subpopulation 5, has the potential to serve as a cancer biomarker for prognosis, as well as a therapeutic target to inhibit metastasis and chemoresistance in cancer [19]. Subpopulations 14 and 15 exhibited high expression of GRB7, which is often co-ampli ed and overexpressed with HER2 in human breast cancers [20].…”
Section: Functional Status Of the Breast Cancer Clusters And Subpopul...mentioning
confidence: 99%
“…Lysosomes also participate in some cancer-related signaling pathways, such as autophagy and apoptosis [ 8 , 9 ]. Recent studies have found that some lysosomal-related mechanisms play a key role in the development of breast cancer and are closely related to drug resistance and prognosis in prostate cancer [ 10 , 11 ]. Although lysosomal-related genes (LRGs) may be promising biomarkers for predicting cancer prognosis [ 12 , 13 ], few studies have focused on establishing LRG-based prognostic models for breast cancer.…”
Section: Introductionmentioning
confidence: 99%